Elite athletes, a rationale for the use of dietary supplements: a practical approach - Ramsbottom, G. R. (PharmaNutrition, 2020)
The general consensus within the scientific community is that an adequate diet can significantly influence athletic performance, without the need for any further or additional supplementation. Nevertheless, the perception, from times of antiquity to the present day, is that taking additional food nutrients will enhance performance. A common rationale for use of supplements by athletes is to gain a `competitive edge`. Current data suggests that the prevalence of supplement use among athletes is in the 40-70% range, depending on the sport and definition or categorization of supplement. Athletes (youth/adult) may be influenced by a coach, fellow team members or administrators. Not all of these `influencers` may possess up to date knowledge with respect to a supplement`s safety, efficacy or known side effects. Ingestion of supplements runs the risk of contamination with compounds banned by WADA (World Anti-Doping Agency). Athlete education, together with the athlete working in close collaboration with his/her health care team is a way to militate against a potential ban and optimize athlete health. Here we present a scientific rationale (with guidelines and case examples) for safe supplement use that should prove of benefit to the competitive athlete.